2022
DOI: 10.1177/00333549211058173
|View full text |Cite
|
Sign up to set email alerts
|

Expanding PrEP Services for Men Who Have Sex With Men and Transgender Persons Through Health Department Programs: Key Processes and Outcomes From Project PrIDE, 2015-2019

Abstract: Objective: Pre-exposure prophylaxis (PrEP) Implementation, Data to Care, and Evaluation (PrIDE) was a demonstration project implemented by 12 state and local health departments during 2015-2019 to expand PrEP services for men who have sex with men (MSM) and transgender persons at risk for HIV infection. We describe findings from the cross-jurisdictional evaluation of the project. Methods: We analyzed work plans, annual progress reports, and aggregate quantitative program data submitted by funded health departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…From the provider perspective, the bridge clinic structure, where several providers might see the same patient while they await connection to longer-term care, also presented some barriers to PrEP delivery adherence support. Patient navigation, through peer or professional supports, has been shown to increase engagement in HIV and substance use treatment in other clinical settings and populations, including PrEP-specific navigation [47][48][49][50][51][52]. This is consistent with our participants' experiences regarding the value of outreach services supporting PrEP adherence and follow-up in community settings [53].…”
Section: Discussionsupporting
confidence: 81%
“…From the provider perspective, the bridge clinic structure, where several providers might see the same patient while they await connection to longer-term care, also presented some barriers to PrEP delivery adherence support. Patient navigation, through peer or professional supports, has been shown to increase engagement in HIV and substance use treatment in other clinical settings and populations, including PrEP-specific navigation [47][48][49][50][51][52]. This is consistent with our participants' experiences regarding the value of outreach services supporting PrEP adherence and follow-up in community settings [53].…”
Section: Discussionsupporting
confidence: 81%
“…PrEP navigation models designed by clinics and community-based organizations that combine professional and peer navigation have been found to be highly effective in linking MSM of color to PrEP [32]. However, even among programs implementing intensive multilevel activities to increase PrEP use, racial and ethnic disparities persisted [33]. Although we found that reported PrEP use among Black partners rose an estimated annual 29.9% from the 2015 to 2019 MMP cycle, the percentage point difference in PrEP use was higher in 2019 compared to 2015 (À11.9 percentage points vs. À7.8 percentage points).…”
Section: Resultsmentioning
confidence: 99%
“…4,5,9 Six of the 7 THRIVE sites are EHE-funded phase 1 jurisdictions. 8 THRIVE laid important groundwork for the ongoing work in the EHE initiative to reduce HIV incidence at least 90% by 2030 through diagnosis, prevention, treatment, and outbreak response. 10 Most THRIVE clients were screened for PrEP, and there were no notable disparities in screening by age or race or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…6 THRIVE activities took place in Birmingham, AL; Baltimore, MD; Washington District of Columbia; New Orleans, LA; Brooklyn, New York City, NY; Philadelphia, PA; and Hampton Roads, VA. New York City, Baltimore, LA, and Virginia departments of health were also recipients of funding through the "Pre-exposure Prophylaxis* Intervention*Data-to-Care-*Evaluation" (PrIDE) project. 8 Project activities to increase the use of PrEP among GBM and TGW, especially among Black and Hispanic or Latino persons, were complementary and intertwined to varying degrees in these jurisdictions. Data on service usage reported here reflect those combined PrIDE and THRIVE activities at cofunded sites but are referred to throughout as THRIVE.…”
Section: Methodsmentioning
confidence: 99%